Upaya Peningkatan Pemahaman Kesehatan Lingkungan melalui Pemanfaatan Sampah Plastik dari Kaleng Cat di Desa Cibiru Wetan, Kabupaten Bandung, Jawa Barat - Widhya Aligita; Soni Muhsinin; Fauzan Zein Muttaqin; Anne Yuliantini; Aiyi Asnawi (Jurnal Pengabdian Pada Masyarakat, 2020)
EFFORTS TO IMPROVE UNDERSTANDING OF ENVIRONMENTAL HEALTH THROUGH UTILIZATION OF PLASTIC WASTE IN CIBIRU WETAN VILLAGE, KABUPATEN BANDUNG, WEST JAWA. Plastic waste can contaminate soil, air, sea, and even air, because plastic is difficult to degrade. Cibiru Wetan Village, Kabupaten Bandung, is a growing area for new housing. As the area grows, the rest of the development becomes waste, such as cans. Cans can hold water and can be a breeding ground for mosquitoes that will interfere with health. One way to reduce this impact is by utilizing can trash into plant pots. Therefore, the purpose of this community service activity was the utilization of tin waste for pots in an effort to increase community awareness in environmental health. The stages of this activity began from providing an understanding of environmental health ranging from understanding, garbage, the environment, health to its use and training in making pots from can garbage material. The results of the activity showed that community participation in this activity was quite high, which meant that awareness to support environmental health began to take shape. In addition, this activity could also improve the ability of participants in the waste recycling process.